2021
DOI: 10.1111/1365-2745.13668
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Pinus sylvestris are more coordinated under local harsher conditions across Europe

Abstract: Plant species that grow across environmental gradients show a range of trait expression, but traits do not vary independently. In fact, phenotypes are integrated expressions of multiple traits that covary due to trade‐offs among functions and processes. Understanding trait covariation structures will ultimately help with predicting species' responses to change and developing management actions. We measured variation and covariation (a proxy of phenotypic integration) among functional traits of Pinus sylvestris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 131 publications
1
14
0
Order By: Relevance
“…Several authors have suggested that stress should lead to higher phenotypic integration, if a tighter and more coordinated phenotype is favoured when resources are limiting (Schlichting, 1986; Gianoli, 2004; Gianoli & Palacio‐López, 2009). However, the adaptive value of increased integration in stress is yet to be determined (Pigliucci, 2003; Merilä & Björklund, 2004; but see Benavides et al ., 2021). Indeed, studies showing the adaptive value of phenotypic integration, regardless of stress level, are very scarce (Damián et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that stress should lead to higher phenotypic integration, if a tighter and more coordinated phenotype is favoured when resources are limiting (Schlichting, 1986; Gianoli, 2004; Gianoli & Palacio‐López, 2009). However, the adaptive value of increased integration in stress is yet to be determined (Pigliucci, 2003; Merilä & Björklund, 2004; but see Benavides et al ., 2021). Indeed, studies showing the adaptive value of phenotypic integration, regardless of stress level, are very scarce (Damián et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also know how fast annual plant populations can change their genetic composition in just a few years due to selection and/or demography (Gómez et al, 2018 ; Kuester et al, 2016 ; Nevo et al, 2012 ; Van Dijk & Hautekèete, 2014 ; Vigouroux et al, 2011 ). On top of that, harsher environments might promote higher phenotypic plasticity (Exposito‐Alonso et al, 2018 ; Lázaro‐Nogal et al, 2015 ; Matesanz et al, 2020 ) and tighter phenotypic integration (Benavides et al, 2021 ; Dwyer & Laughlin, 2017 ; Michelaki et al, 2019 ). For all these reasons, we believe that most annuals will have a chance to thrive in a warmer, more arid, and more seasonal environments by shifting their phenotypic spaces toward new scenarios in which phenotypic integration and seed‐related traits will acquire a higher relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Over generations, a population molds its genetic composition and builds its phenotypic space (Fraebel et al, 2017 ; Murren, 2012 ; Pigliucci, 2007 ; Schlichting & Pigliucci, 1995 ), which encompasses the assemblage of trait combinations of well‐suited phenotypes. One way to understand how the phenotypic space is structured deals with the quantification of among‐ and within‐population genetic variations in phenotypic traits as well as the intrapopulation correlation pattern among traits (Benavides et al, 2021 ; Messier et al, 2018 ). At the population scale, correlations among traits mainly reflect genetic, developmental, or physiological processes (Armbruster et al, 2014 ; Messier et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations